Training in cardiothoracic surgery: the role for simulation - Inam, Hina; Arshad, Hajra; Waqar, Usama; Zaidi, Syeda Maria Ahmad; Ahmed, Shaheer (Journal of the Pakistan Medical Association, 2024)
Adequate cardiothoracic surgical training is essential for provision of quality care to patients. In recent years, simulation-based training has been advocated as an adjunct to traditional surgical training. Advances in simulation technology has resulted in many low- and high-fidelity simulators being employed in cardiothoracic surgical training. Such models allow trainees to practise an array of realistic full-length procedures in a safe and controlled environment, with the window to make mistakes and consider them learning points. There is significant evidence to demonstrate the effectiveness of cardiothoracic surgery simulation in improving surgical skills and operating room performances in addition to building confidence among trainees. However, owing to the high financial cost of arranging it, simulation-based training is not widespread in low- and middle-income countries, including Pakistan. —Continue